Reward Systems and Sustainable Human Resource Management: The Mediating Roles of Employee Commitment, Employee Culture, Situational Leadership, and Employee Performance - Sugiyono; Nera Marinda Machdar; Zahara Tussoleha Rony (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Sustainable Human Resource Management (Sustainable HRM) has become a critical strategic concern as organizations seek to balance performance demands with long-term sustainability. While reward systems are widely recognized as essential HR mechanisms, empirical evidence explaining how they contribute to Sustainable HRM remains limited and inconclusive. This study examines the role of reward systems in fostering Sustainable HRM through the mediating mechanisms of employee commitment, employee culture, situational leadership, and employee performance. Using a quantitative explanatory design, data were collected from 360 managerial-level employees across five companies in West Java, Indonesia. Structural Equation Modeling with Partial Least Squares (PLS-SEM) was employed to test the proposed relationships and mediation effects. The results reveal that reward systems significantly strengthen employee commitment, employee culture, and situational leadership, but do not directly influence employee performance or Sustainable HRM. Among the organizational factors examined, situational leadership emerged as the only significant predictor of employee performance. Furthermore, employee performance was found to have a strong and direct effect on Sustainable HRM, while other variables showed no direct impact. Mediation analysis confirms that employee performance partially mediates the relationship between situational leadership and Sustainable HRM. These findings suggest that reward systems function as foundational enablers rather than direct drivers of sustainability-oriented HR outcomes. Sustainable HRM is achieved primarily through leadership-driven performance mechanisms rather than through reward allocation alone. This study contributes to Sustainable HRM literature by clarifying the internal pathways through which HR practices translate into sustainable outcomes, particularly within emerging economy contexts.